Preoperative Use of Statins in Carotid Artery Stenting: A Systematic Review and Meta-analysis. (October 2018) - Texakalidis, Pavlos; Giannopoulos, Stefanos; Jonnalagadda, Anil K.; Chitale, Rohan V.; Jabbour, Pascal; Armstrong, Ehrin J.; Schwartz, Gregory G.; Kokkinidis, Damianos G.
Purpose: To determine through meta-analysis whether administration of statins before carotid artery stenting (CAS) is associated with fewer periprocedural adverse events.Methods: All randomized and observational English-language studies of periprocedural statin administration prior to CAS that reported the outcomes of interest (stroke, transient ischemic attack, myocardial infarction, and death at 30 days) were included in a random-effects meta-analysis. The I 2 statistic was used to assess heterogeneity. Meta-regression analysis was performed to determine whether an association of statin treatment with risk of outcome events was influenced by other trial-level baseline characteristics of statin-treated and untreated patients.Results: Eleven studies comprising 4088 patients were included. Patients who received statins prior to CAS had a significantly lower risk of stroke (OR 0.39, 95% CI 0.27 to 0.58, p<0.01; I 2 =0%) and death (OR 0.30, 95% CI 0.10 to 0.96, p=0.042; I 2 =0%). Statin use was not associated with a reduced risk of transient ischemic attack or myocardial infarction. In meta-regression analysis, other trial-level baseline characteristics had no significant influence on the association of statin treatment with death or stroke.Conclusion: Statin therapy prior to CAS is associated with decreased risk of perioperative stroke and death without any effect on the rates of transient ischemic attack or myocardial infarction.